Substitusi Tepung Ketan Hitam dengan Penambahan Serbuk Jahe pada Pembuatan Thin Brownies: Mutu Sensori dan Kesukaan Konsumen - Qolbiyatun Nadhifah; Any Sutiadiningsih; Ila Huda P. Dewi; Qorry' Aina (Kampus Akademik Publiser, 2026)
This study aimed to analyze the sensory quality, consumer preference, and nutritional content of black glutinous rice thin brownies with ginger powder addition. A two-stage quantitative experiment was conducted at the Culinary Laboratory, Faculty of Vocational Studies, Universitas Negeri Surabaya. The first stage selected the wheat and black glutinous rice flour ratio (30%:70%, 40%:60%, 50%:50%) assessed by nine trained panelists using the Friedman test, while the second stage evaluated ginger powder addition (2%, 4%, 6%) assessed by 35 panelists using One-Way ANOVA and Duncan tests on a 1-5 hedonic scale. The results showed that the selected flour ratio was 40%:60%, and ginger powder addition significantly affected aroma, taste, texture, and preference, but not color. The best treatment was 4% ginger powder, obtaining the highest preference score (4.23) and containing 58.11% carbohydrate, 31.12% fat, and 6.19% protein. Therefore, 4% ginger powder is recommended as the optimal formulation for black glutinous rice thin brownies.